Kegagalan Komunikasi Matematis Siswa dal am Pemecahan Masalah ditinjau Berdasarkan Karakterisiknya - Sumaji, Sumaji (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
Mathematics communication could develop conceptual understanding and mathematics problem-solving and reasoning. An excellent mathematics communication influences the problem-solving of learners. The mathematics communication skill characteristics are rigorousness, economy, and freedom. This research aimed to describe the learners’ mathematical communication failures in solving problems reviewed from the characteristics. This research is qualitative. There were 30 graders of VIII grade of Islamic JHS Maslakhul Huda, Sluke, Rembang. This research selected two learners that failed to communicate their problem-solving results based on the characteristics. The instruments to collect data were problem-solving tasks and interview guidelines. The findings showed that: (1) the learners that failed to communicate the problem-solving results only met the rigorousness and freedom characteristics, and (2) these learners only had rigorousness characteristics.